STRATEGI BADAN KEPEGAWAIAN DAERAH PROVINSI JAWA TENGAH DALAM MENINGKATKAN KAPASITAS PEGAWAI NEGERI SIPIL DAERAH (STUDI KASUS:BIRO HUBUNGAN MASYARAKAT DAN DINAS PENGELOLAAN SUMBER DAYA AIR) - Ridho Al Sandra; Budi Setiyono; Nunik Retno H (Journal of Politic and Government Studies, 2015)
AbstractPathology of a bureaucracy that spread now were already be a hindrancewhich remarkable massive to create Indonesia bureaucracy according to the goodgovernance concept. PP no.8 year 2003 is an effort from the government for themissions trimming bureaucracy in Indonesia from year to year to make it moreefficient . Massive bureaucratic will not be worth if not accompanied by sufficientcapacity of civil servants. The capacity of a bureaucrat own can be seen from thebackground of their education and performed periodically test. BKD is agovernment agency who served as the coordinator and accommodate SKPD forcivil servants developement problems with making efforts and formulatingstrategies to face capacity building civil servants problems in the neighborhood ofgovernment of the Central Java Province.This research is using qualitative descriptive methods. Data collection techniquesthrough documentation and interview. The purpose of this research is to find outBKD’s strategy to realizing capacity building program and mechanism of capacitybuilding strategy which applied to Biro Humas and Dinas PSDA of Central JavaProvince which will be used to formulate recommendations as a form of input inthe sustainability of the implementation capacity building program.In realization of his strategy BKD of Central Java Province having six programswhich are included in the capacity building strategy of regional civil servants.Capacity building strategy formulated by BKD of Central Java Province wasfound on the planning process of human resources, procurement CPNS,Placement of civil servants, civil servants assessment centre, education andtraining program also finally the program of study task and a permit learning (formal education ). The mechanism of the capacity building strategy BKD CentralJava Province still need to more optimal effort from actors of implementingcapacity building. BKD so far is considered by civil servants in Biro Humas danDinas PSDA Central Java Province still just a socialization through circulars onlyhad not been the facilitator to the whole strategyIn an effort to run the strategy capacity building program that can berecommended to BKD among other is individual capacity building programbefore entering to capacity building in the level of institutional .Increasing thequality of training so that existing material in training and BINTEK has to bespecific and more substantial according it takes civil servants in each SKPD. Themechanism for own assessment centre shall be imposed on all of the civil servantswho are in the government of central java province especially in Biro Humas danDinas PSDA of Central Java Province. Because in an organization all parts have afunction in running the authority and duty, not only contains leaders who made apolicy but including staff and employees who runs the policy.Keyword : bureaucracy, capacity building strategy, mechanism